Communication-enhancing vagueness - Daniel H. Wood (Games, 2022)
I experimentally investigate how vague language changes the nature of communication in a biased strategic information transmission game. Counterintuitively, when both precise and imprecise messages can be sent, in aggregate, senders are more accurate, and receivers trust them more than when only precise messages can be sent. I also develop and structurally estimate a model showing that vague messages increase communication between boundedly rational players, especially if some senders are moderately honest. Moderately honest senders avoid stating an outright lie by using vague messages to hedge them. Then, precise messages are more informative because there are fewer precise lies.
Keywords: C91; D03; D83; 330; bounded rationality; cheap talk; deception; experiments; honesty; vagueness